1995
DOI: 10.1063/1.115293
|View full text |Cite
|
Sign up to set email alerts
|

Metallization to asymmetric cladding separate confinement heterostructure lasers

Abstract: Annealed and nonannealed p-contact metallization for asymmetric cladding separate confinement heterostructure lasers with a thin p-cladding layer is reported. Ti–Au and annealed Ti–Pt–Au p-type contacts are demonstrated to improve the adhesion over a pure gold contact and allow annealing of the metallization to thin p-cladding laser structures at the expense of an increase in the optical loss. The increased optical loss is due to the decreased conductivity of titanium and platinum as compared to gold. As littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The electrode, a 2 µm thick gold layer, was deposited on the BST film to complete the circuit fabrication. To enhance the adhesion between the BST thin film and the gold electrode [5], a thin Cr adhesion layer was deposited prior to Au deposition. The final geometries of the interdigital capacitor (IDC), similar to those of Ref.…”
Section: Methodsmentioning
confidence: 99%
“…The electrode, a 2 µm thick gold layer, was deposited on the BST film to complete the circuit fabrication. To enhance the adhesion between the BST thin film and the gold electrode [5], a thin Cr adhesion layer was deposited prior to Au deposition. The final geometries of the interdigital capacitor (IDC), similar to those of Ref.…”
Section: Methodsmentioning
confidence: 99%
“…͑4͒, underlines the viability of the shallow-waveguide approach, even though we used simple Ni-Au for the p-type ͑top͒ metallization instead of the more elaborate ''shiny'' contacts developed elsewhere. 14,15 Further improvements are obvious: By using the narrower stripes of a normal single-mode laser, the threshold current can be decreased significantly and the fabricationrelated variations of the microstructured mirror across its width can be reduced, which should lead to a ''cleaner'' mirror response. By fabricating lasers with a microstructured front and back mirror, the thresholds well below 1 mA that have been predicted for devices of this type 3 will come within reach.…”
Section: Discussionmentioning
confidence: 99%
“…Metallic mirrors serve as ohmic contacts as well as reflectivity enhancer in lasers and LEDs (Baba et al 1996; Chang-Hasnain et al 1991; Hunt et al 1993; Katz 1995; Luo and Zory 1990; Smith et al 1995). It has been observed that wetting metals like Palladium and Titanium provide reliable adhesion and better ohmic contacts (Yang et al 1990).…”
Section: Introductionmentioning
confidence: 99%